PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VII.A SMP NEGERI 3 BANGKO TAHUN PELAJARAN 2015-2016 - Saputra, Junaidi Aidil; Natalina, Mariani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research conducted at VII.A class of SMPN 3 Bangko the 2015/2016 school year to improve student learning outcomes by implementing cooperative learning model STAD. This research is a classroom action research conducted in two cycles of planning, implementation, observation and reflection. The parameters in this study is the thoroughness of learning outcomes derived from the value of post tets and the daily test, student activities and teacher's activities and there are collected using observation sheet. The results showed increased absorbency where first post test is 75.20 into 79.50 in post test 2, while the second cycle value increased 85.00 first post test on second post test to 90.6. Mastery learning increased from the first cycle that 74.55 (enough), being 80.70 (both) in the second cycle. Choice group increased from the first cycle, four great groups and one group of super, into three great groups and two groups of super in the second cycle. Student activity increased from the first cycle average of 81.73% to 94.04% in the second cycle. Teacher activity increased from the first cycle an average of 75% (enough), to an average of 95% (excellent) on the second cycle. It can be concluded that the implementation of cooperative learning model STAD can improve learning outcomes of VII.A grade science students at SMPN 3 Bangko 2015/2016 school year.Keywords : Cooperative Learning Type STAD, Learning achievement2